STRATEGI MENJUAL BERBASIS MARKETPLACE PADA PRODUK UNGGULAN KAMPOENG KAJOETANGAN HERITAGE - Bunyamin; Nunung Nurastuti U.; St Munfaqiroh; Sugeng H; Kadarusman; Fera Tj; Setyawan; Imama Z; Ali L; Triana M (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2021)
To minimize the spread of covid 19, the mobile marketplace is one alternative to get around the prohibition on meeting directly between sellers and buyers to reduce the spread of covid-19 but still encourage economic movement, especially sales of production. The method in this service is carried out by discussing and demonstrating the use of the mobile marketplace. The result is that the flagship product business group Kampoeng Kajoetangan Heritage is starting to be able to use a good mobile marketplace to sell the products they produce By using the marketplace technique, it is expected to increase profits on sales because the market reach will be wider.